Inventory management application system at PT Bank Sinarmas Tebing Tinggi Jambi - Okka Raisa Lestari; Rosmenda Purnama Devi (Journal of Applied Accounting And Business, 2019)
This research aims to suggest an improvement to management procedure of office stationery inventory through an application system of office stationery inventory for PT Bank Sinarmas Tebing Tinggi Jambi. In this research, the application systems facilitate office stationery in-out transactions and amount of stock remaining. It helps PT Bank Sinarmas Tebing Tinggi Jambi to perform well-organized inventory.Design research of this study is a descriptive research with case study approach. Inventory systems of office stationery were made using web based. For database, this study used MySQL database with PHP language program. Tool for system development used data flow diagram and tool for system design used entity relational database. System development method used waterfall approached.Results of this research show that information systems of office stationery web-based can used to inform merchandise (type of office stationery) menu, in-out merchandise, and stock opname. This application also provide reports for those informations.